An in situ toxicity assay with the local phytoplankton community - Moreira-Santos, M
The present study describes an approach for toxicity estimates based on the in situ exposure of the local phytoplankton community immobilized in calcium alginate beads The assay was deployed in an acid mine drainage-impacted system at a reference site and an impacted site Abundances and growth rates of major taxonomic groups (green algae flagellates diatoms and cyanobacteria) and of the entire community were measured The ecological relevance of classical toxicity estimates was evaluated by performing in situ and laboratory assays with the standard species Pseudokirchneriella subcapitata and Chlorella vulgarly Site waters were tested without and with nutrient enrichment to discriminate toxic effects from those caused by nutrient limitations Despite the occurrence of growth limiting conditions for the local phytoplankton within the alginate matrix an impact of the mine effluent on the community was detected The growth of the community and of all taxonomic groups except for the cyanobacteria was less at the impacted site than at the reference site although adding nutrients partially compensated for the effluent detrimental effects Shifts in the community structure were also provoked by the mine effluent decreases in the abundance of green algae were paralleled by Increases in the abundance of flagellates and diatoms but mainly of cyanobacteria Effects on the growth of both standard species of green algae were in conformity with those on the local phytoplankton probably because the latter was dominated by green algae Although future improvements regarding the cell immobilization technique should be attempted the proposed easy and inexpensive approach to assess both the growth and the structure of local phytoplankton communities will allow more environmentally realistic site specific assessments of water quality Environ Toxicol Chem 2011 30 196-205 (C) 2010 SETAC